Sexual Response Problems and Their Correlates Among Older Adults From the Sexual Well-Being (SWELL) Study in China: Multicenter Cross-Sectional Study - Bingyu Liang; Chen Xu; Bingyi Wang; Xinyi Li; Xin Peng; Ying Wang; Hui Li; Yong Lu; Xiaopei Shen; Lin Ouyang; Guohui Wu; Maohe Yu; et al. (JMIR Aging)
Abstract BackgroundSexual response problems among older adults are not an inevitable consequence of aging but rather a response to sexual health. However, there is a lack of recent and multicenter data on this issue in China. ObjectiveThis study aims to assess the prevalence of sexual response problems and their correlates among older adults. MethodsA multicenter cross-sectional study on sexual well-being was conducted among individuals aged more than 50 years in China between June 2020 and December 2022. Data on sociodemographics, physical health, psychological health, and sexual response problems were collected through face-to-face interviews. We included sexually active older adults who reported either vaginal, oral, or anal sex in the past 12 months for this study. Sexual response problems included a lack of interest or enjoyment in sex; feeling anxious, having pain, or no excitement during sex; no desire or orgasms; and the lack of lubrication in sex. The stepwise logistic regression models were used to examine the correlates of sexual response problems. ResultsA total of 1317 sexually active older adults (842 men, 475 women) were included. Older women reported a higher prevalence of sexual response problems than older men (52.0% [247/475] vs 43.1% [363/842]). Common factors associated with at least one of the sexual response problems included living in rural areas (men: adjusted odds ratio [aOR]=0.31, 95% CI 0.22‐0.43; women: aOR=0.29, 95% CI 0.19‐0.43) and abnormal BMI (aOR=men: 1.52, 95% CI1.11‐2.07; women: aOR=2.19, 95% CI 1.47‐3.28). Among older men, sleep quality (aOR=1.87, 95% CI 1.30‐2.68), emotional connection with sex partners during sexual intercourse (aOR=0.69, 95% CI 0.50‐0.96), frequently experienced fatigue (aOR=2.47, 95% CI 1.59‐3.90), anxiety (aOR=4.26, 95% CI 1.12‐21.27), and seeking professional help for sex life (aOR=1.58, 95% CI 1.14‐2.21) were associated with sexual response problems. Among older women, sexual response problems were associated with a lack of physical exercise (aOR=1.69, 95% CI 1.13‐2.54), poor sex-partner relationships (aOR=1.70, 95% CI 1.12‐2.60), and depressive symptoms (aOR=3.18, 95% CI 1.18‐10.24). ConclusionsSexual response problems are common among older adults. These problems were associated with adverse physical health, mental health, and poor sex-partner relationships. These findings highlight the importance for health care providers to take into account the physical and psychological health of older adults, as well as the quality of their relationships with sexual partners when diagnosing and addressing sexual response problems.